TITO-type current-mode universal filter with one active element - Supavarasuwat, Piya; Kumngern, Montree (My University, 2015)
This paper presents a new current-mode universal filter with two-input two-output using only one fully differential current conveyor, two grounded capacitors and two grounded resistors. The use of grounded passive components makes the proposed structure highly for integrated circuit implementation. The proposed filter provides low-pass, band-pass, high-pass, band-stop and all-pass current responses into a single topology with no passive-value matching condition requirements. The natural frequency and the quality factor can be controlled orthogonally by setting the value of the passive components. The workability of the proposed circuit is confirmed using PSPICE simulators.
Keywords: current-mode circuit; fully differential current conveyor; Universal filter